Synthesis and Biological Activity Evaluation of Novel 5-Methyl-7-phenyl-3H-thiazolo[4,5-b]pyridin-2-ones - Andrii Lozynskyi; Yulian Konechnyi; Julia Senkiv; Ihor Yushyn; Dmytro Khyluk; Olexandr Karpenko; Yulia Shepeta; Roman Lesyk (MDPI AG, 2021)
A series of 5-methyl-7-phenyl-3H-thiazolo[4,5-b]pyridin-2-ones has been designed, synthesized, and characterized by spectral data. Target compounds were screened for their antimicrobial activity against some pathogenic bacteria and fungi, and most of them showed moderate activity, especially compound 3g, which displayed the potent inhibitory effect against Pseudomonas aeruginosa and Escherichia coli with MIC value of 0.21 μM. The active thiazolopyridine derivatives 3c, 3f, and 3g were screened for their cytotoxicity effects on HaCat, Balb/c 3T3 cells using MTT assay, which revealed promising results. In silico assessment for compounds 3c, 3f, and 3g also revealed suitable drug-like parameters and ADME properties. The binding interactions of the most active compound 3g were performed through molecular docking against MurD and DNA gyrase, with binding energies and an inhibitory constant compared to the reference drug ciprofloxacin. The tested thiazolo[4,5-b]pyridines constitute an exciting background for the further development of new synthetic antimicrobial agents.